(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the psychological and pedagogical aspects of the process of formation of computational thinking. Computational thinking plays an important role in developing skills that meet the requirements of the modern information age and digital technologies. The study analyzes pedagogical methods, tools and psychological approaches used to develop computational thinking among schoolchildren and students. The authors note that computational thinking includes algorithmic, logical and systems thinking, and also emphasize the important role of teachers in the effective organization of this process. In addition, examples of how these skills can be developed through digital training programs and trainings are considered.